Synthesis of Layered Double Hydroxides Intercalated With Drugs for Controlled Release: Successful Intercalation of Ibuprofen and Failed Intercalation of Paracetamol - Luengo, Carina Vanesa (2022)
This work examines the effect of drug structure and ionization degree on the formation and properties of biocompatible layered double hydroxides (LDH) intercalated with ibuprofen and paracetamol. Ibuprofen (pKa 1⁄4 5.3) is in its anionic form, whereas paracetamol (pKa 9.4) is only partially ionized at the synthesis pH (9.0), and thus intercalation is expected to be different in the two cases. Chemical analyses, X-ray diffraction, electron microscopy, infrared spectroscopy and thermal analyses were applied to characterize the materials. Dissolution kinetics and drug release kinetics were also investigated, in an ample range of pH (3.0e9.0) in NaCl solutions, and in physiological buffers (1.2, 4.5 and 6.8). All characterization tech- niques showed that an efficient intercalation of ibuprofen took place, resulting in a material with 30% of its weight corresponding to the drug. On the contrary, all techniques revealed a very poor intercalation of paracetamol (1.2%). The dissolution kinetics of LDHs was highly pH-dependent, being higher as pH decreased. The drug release kinetics, conversely, increased as pH increased. In physiological buffers the release rate depended not only on the pH but also on the type of buffer. This last behavior is useful to control the release in different parts of the digestive system.